The impact of the Russian-Ukrainian war on European defense policy: a study of the geopolitical and security dimensions - Israa Khalil Majeed (Tikrit Journal For Political Science, 2024)
The study deals with the development of Eu's defense policy after the Russian war on Ukraine in February 2022. The Russian war on Ukraine contributed to the emergence of security and geopolitical dimensions and challenges for Europe, most notably the growth of the Russian nuclear threat and the decline of the US security role in Europe. Which in turn forced the Europeans to develop European defense policy and also move forward with steps towards complete defense autonomy. The most prominent manifestations of this development were the significant increase in military spending and the launch of a program for European defense industries. Despite the unprecedented developments after 2022, these developments face some challenges, most notably the challenge of military spending and the continued absolute confidence in the American protection umbrella. As a result, achieving complete defense autonomy for Europe is an impossible matter. Keywords: European Union, Russia, Defense Autonomy, United States, Balance Of Threat, Strategic Compass.